Desarrollo, sostenibilidad y capacidades: una trilogía indesligable - Solano, David (2007)
The difference between economic growth and development has been debated for long. Classical economists hold that the most important challenge for a country was to create wealth. However, as time goes by, other important and complementary concepts have arisen such as development, sustainable development and social capital, stressing out the need for creating human, institutional and natural capacities to generate lasting well-being. Capacities do not come besides investment; we need to create them. However, some examples show that many public and private decision-makers in Peru do not take into account such need; they prioritize economic capacities and neglect social, environmental and institutional ones. Development is not be possible without capacity building, and once the proper capacities are built may sustainable development be created.